Economic Diversification and Human Development in South Asia. (August 2019) - Ali, Muhammad; Memon, Manzoor Hussain
The paper examines the effect of diversification on social welfare in South Asia using the macroeconomic data for the period 1996–2011, with export diversification as a proxy of economic diversification. In this paper, three types of diversification are assessed (i.e. related, unrelated, and overall variety). While unrelated variety and overall variety show increasing trend over the years, related variety seems to show a non-linear inverted U-shaped curve. Estimation results reveal that all three types of variety have a positive and significant relationship with human development in South Asia, which shows that diversification is beneficial for human development in South Asian countries. It is also found that the existing level of human capital significantly moderates the relationship between related variety and social welfare.